PEMBELAJARAN INOVATIF- PROGRESIF: (Konsep Dasar dan Implementasinya) - Rusnawati (JURNAL EKSPERIMENTAL : Media Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2019)
As the time goes, it has had a big effect to knowledge and learning. One of the changes of the paradigm was earlier learning orientation that focused on teacher (teacher center). Nowadays it is concentrated in students. The earlier methods were more dominated by expository, while at present is participatory. The approach used earlier were more textual but now contextual. A learning process is not only studying about concept, theory or fact but also daily application. Hence, the materials of learning are not only consisted of simple entitities such as memorizing and understanding but also concerning on more complex materials which needed analysis, application and synthesis.one of innovations which is interesting is the raise of Innovative progressive learning or better known as learning practice. The research statements were what Innovative progressive learning is. What is the characteristics of Innovative progressive learning. What are the examples of Innovative progressive learning. How are the implications of Innovative progressive learningin learning components. To find the data the researcher employed qualitative methods i.e literature study. the result indicated that Innovative progressive learning means the innovation of learning designed to aid students to understand theory or concepts through learning experience.